High-temperature wear behaviour of ZrC/NbC-reinforced CrMnFeCoNi coatings. (2nd September 2022) - Sun, Da; Cai, Yangchuan; Zhu, Lisong; Han, Jian
ABSTRACT: Nowadays, studies of high entropy alloys (HEAs) have shown excellent properties. To improve the high-temperature wear resistance of CrMnFeCoNi alloy, refractory carbides (NbC and ZrC, respectively) reinforced CrMnFeCoNi composite coating were prepared by laser cladding (LC), and its wear performance was investigated. The composite coating showed no cracks or other defects that had metallurgical bonding with the substrate. Those coatings exhibited oxidative and adhesive wear mechanisms in reciprocating wear tests at 600°C. In contrast to the strengthening of NbC, the ZrC in the coating rapidly oxidized during high-temperature wear, forming a large amount of ZrO2 . These oxides formed in wear promote the formation of a protective film, further improving the oxidation resistance and wear resistance of the coating.